Assessment of Post-transplantation Liver Function Tests in Patients Undergoing Allogeneic Stem Cell Transplantation - Melih Kızıltepe; Esra Yıldızhan; Ali Ünal; Mustafa Çetin; Bülent Eser; Leylagül Kaynar (Erciyes Medical Journal, 2020)
Objective: Allogeneic hematopoietic stem cell transplantation is a treatment with a considerable rate of complete cure in hematological disorders. Hepatic complications are common causes of morbidity and mortality affecting the survival after stem cell transplantation. This study was conducted to identify risk factors for hepatic dysfunction and related potential factors affecting the survival in patients undergoing allogeneic hematopoietic stem cell transplantation. Materials and Methods: We retrospectively evaluated the data from 300 allogeneic hematopoietic stem cell transplantation recipients between March 2004 and May 2014 in the Erciyes University Hematology and Bone Marrow Transplantation Center, Turkey. The study included 300 patients and their serial monitorization of the liver function tests, examined before and after transplantation. Results: The transplantation in 30 patients was performed from haploidentical donors and in 13 patients from unrelated donors. We identified the liver function abnormalities in 71.7% of patients in the post-transplantation period. The most common causes were graft-versus-host disease (43.6%), drug toxicity (24.7%), and sepsis (13.9%). Post-transplantation liver abnormalities were more common in patients with acute leukemia (p=0.02), iron overload (p<0.001), and in those who also had transaminitis in the pretransplantation period (p<0.001). Relapsed underlying disease (p<0.001), iron overload, and a bilirubin level >2 mg/dL in association with hepatic dysfunction during the post-transplantation period were identified as major factors influencing mortality following transplantation (p<0.001). Conclusion: We concluded that liver function abnormalities are frequent in the hematopoietic stem cell transplantation process. For a successful management, it is important to monitor the liver function and to identify additional risk factors before and after transplantation.